Professional Teaching Ethos: A route composed by discourses and knowledges (Revista Internacional de Formação de Professores, 2021)
In this article we carried out an incursion through paths of construction of the professional teaching ethos in the area of Letters - Portuguese Language which reflects about humanities as the basis for formation and also the connection thread running through completeness of the skills to teach. The construction of professional ethos occurs through anthropological-constituent implementation by means of materialized dialogical structures by communication. Methodologically, we took as discursive resource interviews with teachers, having the conductive line a question which addresses in the categorical, ideological and experiential dimensions to find out how the construction of the ethos takes place. The results insert the identification teaching professionalism embedded in beliefs and knowledge.
Keywords: Teaching Ethos.; Professional teaching.; Competences.; Knowledge.